TAM-full object-verb order in the Mbam languages of Cameroon - Mous, Maarten (ZAS Papers in Linguistics, 2014)
Nen and Nyokon are unique among the Bantu languages in allowing full nominal objects between the tense/aspect marker and the verb. Despite the fact that the two languages are neighbours and related they make different use of this positional option. In Nen the position is the default one for objects and the post-verbal position renders an object discrete and suitable for quantified objects and for contrast. In Nyokon the position before the verb is functionally equivalent to the one after the verb. The difference is related to the fact that Nyokon allows the preverbal object only in certain tenses whereas in Nen it is not restricted. But contrasted objects in Nyokon too appear after the verb. There is a construction in which both positions are filled with a constituent. This construction is modelled on a secondary predication construction.